2012
DOI: 10.5430/ijhe.v1n2p43
|View full text |Cite
|
Sign up to set email alerts
|

Examining Mobile Technology in Higher Education: Handheld Devices In and Out of the Classroom

Abstract: This study followed an innovative introduction of mobile technology (i.e., BlackBerry ® devices) to a graduate level business program and documented students' use of the technology from the time students received the devices to the end of their first term of study. Students found the BlackBerry ® device easy to use, and were optimistic regarding its potential role as an instructional tool. Students were self-directed in their use of the devices and found ways to use them within and outside of their classroom e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Numerous studies reveal that students predict a positive impact from mobile learning. That is, students think that mobile phones help them engage with relevant material and raise their confidence as learners (Mueller et al 2012). Moreover, those mobile phones and apps contain many categories having learning tools and traits, short, mid, and final exams notifications, learning videos issued by teaching staff, and others that achieve success for students' learning process (Sass 2015).…”
Section: The Role Of Mobile Apps For Higher Educationmentioning
confidence: 99%
“…Numerous studies reveal that students predict a positive impact from mobile learning. That is, students think that mobile phones help them engage with relevant material and raise their confidence as learners (Mueller et al 2012). Moreover, those mobile phones and apps contain many categories having learning tools and traits, short, mid, and final exams notifications, learning videos issued by teaching staff, and others that achieve success for students' learning process (Sass 2015).…”
Section: The Role Of Mobile Apps For Higher Educationmentioning
confidence: 99%
“…Mueller, Wood, Pasquale and Cruikshank [3] studied the use of mobile (handheld) devices in higher education. The methodology of longitudinal analysis was adopted in this study.…”
Section: Mobile Wltsmentioning
confidence: 99%
“…Absence of student interest and motivation in the use of technology for learning will reduce the intended positive outcomes of the technology. The researchers suggested that student participation in identifying device uses for learning and teaching purposes increases student participation with the mobile devices [3].…”
Section: Mobile Wltsmentioning
confidence: 99%
“…In addition, Muller, et al (2012) explain that mobile technologies have the potential to facilitate outside learning activities with a high impact on motivation.…”
Section: Introductionmentioning
confidence: 99%